1986
DOI: 10.1007/bf00511404
|View full text |Cite
|
Sign up to set email alerts
|

Human myocardial ?-adrenoceptors: demonstration of both ?-adrenoceptors: mediating contractile responses to ?-agonists on the isolated right atrium

Abstract: On the isolated electrically driven muscle strip of human right atrial appendages the beta-adrenoceptor subtypes mediating the positive inotropic effects of isoprenaline, dobutamine and procaterol were characterized using the beta 1-selective antagonist bisoprolol and the beta 2-selective antagonist ICI 118,551. The three agonists induced concentration-dependent increases in force of contraction with an order of potency: procaterol (pD2-value: 8.03) greater than isoprenaline (pD2-value: 7.73) greater than dobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…In a recent study, we demonstrated that ␤ 1 -AR-mediated chronotropic responses in right atria of STZ-induced diabetic rats are impaired, but those mediated via ␤ 2 -ARs are preserved (9). It has also been demonstrated that in the human atrium, both ␤ 1 -and ␤ 2 -ARs are functionally coupled to the adenylate cyclase system (10), and both subtypes of ␤-ARs are reported to contribute to the cardiac responses of ␤-AR agonists (11). Thus it has been suggested that, in the human right atrium, both ␤ 1 -and ␤ 2 -ARs are involved in the physiological regulation of the force of contraction and/or heart rate.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…In a recent study, we demonstrated that ␤ 1 -AR-mediated chronotropic responses in right atria of STZ-induced diabetic rats are impaired, but those mediated via ␤ 2 -ARs are preserved (9). It has also been demonstrated that in the human atrium, both ␤ 1 -and ␤ 2 -ARs are functionally coupled to the adenylate cyclase system (10), and both subtypes of ␤-ARs are reported to contribute to the cardiac responses of ␤-AR agonists (11). Thus it has been suggested that, in the human right atrium, both ␤ 1 -and ␤ 2 -ARs are involved in the physiological regulation of the force of contraction and/or heart rate.…”
mentioning
confidence: 79%
“…In those studies, however, ␤-ARs were not differentiated according to their subtypes. ␤-ARs of both the ␤ 1 and ␤ 2 subtypes have been reported to coexist in certain cardiac tissues (10,11). Human cardiac ␤ 1 -and ␤ 2 -ARs are coupled to adenylate cyclase through the G s protein.…”
Section: Discussionmentioning
confidence: 99%
“…As a result the blocking potency of (-)atenolol would be greater against (-)-noradrenaline (mostly acts through f1-adrenoceptors) than against (-)-adrenaline (acts through both #1-and f2-adrenoceptors); this was indeed observed. Evidence with physiological catecholamines (Gille et al, 1985;Kaumann & Lobnig, 1986;Kaumann & Lemoine, 1987) and non-physiological agonists (Mugge et al, 1985;Bristow et al, 1986;Zerkowski et al, 1986) Hall et al (1988). They observed that (-)-adrenaline (but not (-)-noradrenaline) was a more potent inotropic stimulant on atria from (-)atenolol-treated than on those from untreated patients and that the enhanced responses were not affected by selective blockade of fi1-adrenoceptors but eliminated by selective blockade of #2-adrenoceptors.…”
Section: The Fractional Stimulation By (-)-Noradrenaline Andmentioning
confidence: 99%
“…Additionally, some inotropic support is provided by direct stimulation of cardiac P2-adrenoceptors, by activation of reflex mechanisms arising from the vasodepressor action and by inhibition of uptake, which results in potentiation of the action of noradrenaline on P,-adrenoceptors (Smith & O'Connor, 1988). Although PI-adrenoceptors predominate over P2-adrenoceptors in the human heart (Bristow et al, 1986;Bohm et al, 1989;Brodde et al, 1989;Steinfath et al, 1991), the smaller P2-adrenoceptor population which also mediates contractile responses (Ablad et al, 1974;Zerkowski et al, 1986) may become more important in some forms of heart disease.…”
Section: Introductionmentioning
confidence: 99%